Do Internships Pay Off? The Effects of Student Internships on Earnings - Shushanik Margaryan; Nils Saniter; Mathias Schumann; Thomas Siedler (Institute of Labor Economics (IZA), 2019)
This paper studies the causal effect of student internship experience in firms on earnings later in life. We use mandatory firm internships at German universities as an instrument for doing a firm internship while attending university. Employing longitudinal data from graduate surveys, we find positive and significant earnings returns of about 6% in both OLS and IV regressions. The positive returns are particularly pronounced for individuals and areas of study that are characterized by a weak labor market orientation. The empirical findings show that graduates who completed a firm internship face a lower risk of unemployment during the first year of their careers, suggesting a smoother transition to the labor market.
Keywords: I23; J01; J31; 330; internships; skill development; higher education; labor market returns; instrumental variable